The expectations of project managers from artificial intelligence: A Delphi study - Holzmann, V. Zitter, D. and Peshkess, S. (Project Management Journal)
Artificial intelligence (AI) technologies are rapidly developing these days and are expected to impact the field of project management on multiple levels; however, there remains a high level of uncertainty regarding the effect that AI might have on project management practices. This article aims to address this topic based on a Delphi study with a panel of 52 project management experts who reflected on future potential AI applications for the project management Knowledge Areas. The article provides a visionary perspective that can be further translated into practical solutions in the near and far future to improve project management practices.- Reproduced
Keywords: Artificial intelligence, project management, Delphi study